b/11-7b=24/11

Simple and best practice solution for b/11-7b=24/11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b/11-7b=24/11 equation:



b/11-7b=24/11
We move all terms to the left:
b/11-7b-(24/11)=0
We add all the numbers together, and all the variables
b/11-7b-(+24/11)=0
We add all the numbers together, and all the variables
-7b+b/11-(+24/11)=0
We get rid of parentheses
-7b+b/11-24/11=0
We multiply all the terms by the denominator
-7b*11+b-24=0
We add all the numbers together, and all the variables
b-7b*11-24=0
Wy multiply elements
b-77b-24=0
We add all the numbers together, and all the variables
-76b-24=0
We move all terms containing b to the left, all other terms to the right
-76b=24
b=24/-76
b=-6/19

See similar equations:

| 4x+2(4x-8)-4=-56 | | X+1/8x=126 | | y/10-70=-67 | | 2×5x=4x | | 10.9+3x-5=13 | | -214=5(7x+2)-3x | | (d)=25+20d | | 2x-3x+4=1 | | (4y+32)-7=15 | | -u+18=201 | | 10=v-1 | | -13.13-13.2z=-3.1z | | p/3+4=5 | | -5(x-3)=-4(x-6) | | 4.97+1.97+(x/2)=12.92 | | -3(11r+5)=3(-9r+9) | | 2p+p+(2)(9)=3p+18 | | 29-15x=-x-3 | | -19+15b-17=-15+12b | | y=(93)93+40 | | 8+2y-8=3(y-11) | | 2=g/6-2 | | -x+7=−x+7=-4x-20 | | -4(1-p)=6(p-2) | | 5x+7x=9x-3 | | |2x+4|=30 | | 13(m-2)=-2(-2m+6) | | 5x-36=x+20 | | r/3+7/3=-5 | | 4d-20=60 | | 20+11u=6u-20-20 | | 2x-81=100 |

Equations solver categories